1987
DOI: 10.2960/j.v7.a16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Allocation and Stratification Strategies on Precision of Survey Abundance Estimates for Atlantic Cod (Gadus morhua) on the Eastern Scotian Shelf

Abstract: One of the primary uses of bottom-trawl survey data, with respect to fisheries management, is the estimation of abundance of the species involved. Stratified-random surveys have been conducted on the eastern Scotian Shelf since 1970. The precision of abundance estimates for Atlantic cod (ages 5-12) from these surveys was found to be inferior to what would have been obtained if simple random surveys had been conducted. These results were primarily due to suboptimal allocation of stations to strata. Historical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 1 publication
1
32
1
Order By: Relevance
“…The spatial distribution of American lobster is influenced by many factors such as temperature (Aiken and Waddy, 1986), salinity (Jury et al, 1994), and shelter availability (Wahle and Steneck 1991) and it differs greatly by season, sex, and size class (Chen et al, 2006). Chang et al, (2010) developed a habitat modeling approach for quantifying season-, size-, and sex-specific lobster distribution in the Gulf of Maine.…”
Section: Simulation Of a "True" Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…The spatial distribution of American lobster is influenced by many factors such as temperature (Aiken and Waddy, 1986), salinity (Jury et al, 1994), and shelter availability (Wahle and Steneck 1991) and it differs greatly by season, sex, and size class (Chen et al, 2006). Chang et al, (2010) developed a habitat modeling approach for quantifying season-, size-, and sex-specific lobster distribution in the Gulf of Maine.…”
Section: Simulation Of a "True" Populationmentioning
confidence: 99%
“…For a stratified random designed survey, many studies revealed that optimizing either sample allocation schemes or stratification schemes could lead to an increased precision of survey means or total estimates (Folmer and Pennington, 2000;Gavaris and Smith, 1987;Smith and Tremblay, 2003). There are many methods for allocating samples among strata, the most common being to allocate samples in proportion to strata area/size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correct design-based approach in this situation is to use cluster sampling formulas, with the transect being the primary unit and the integrated segments of cruise track (referred to as EDSUs in some literature) as secondary units. Key works on the design of hydroacoustic surveys include Francis (1984), Gavaris and Smith (1987), Jurvelius and Auvinen (1989), and Jolly and Hampton (1990). A special ICES workshop held in 1992 (ICES, 1993) reviewed designand model-based approaches for hydroacoustic stock assessment.…”
Section: Design-based Methods For Hydroacoustic Surveysmentioning
confidence: 99%
“…Pennington, 1986;Smith, 1988b;McConnaughey and Conquest, 1993) or modifying aspects of the survey design (e.g. Francis, 1984;Heisey and Hoenig, 1986;Gavaris and Smith, 1987;Jolly and Hampton, 1990;Smith and Gavaris, 1993). Smith (1990) discussed the application of statistical models and their specific estimators to survey data, and showed that biased estimates can easily result from such an approach (see also Jolly and Hampton, 1990;Myers and Pepin, 1990).…”
Section: Introductionmentioning
confidence: 99%